Polyamines in Microalgae: Something Borrowed, Something New - Hung-Yun Lin; Han-Jia Lin (Marine Drugs, 2018)
Microalgae of different evolutionary origins are typically found in rivers, lakes, and oceans, providing more than 45% of global primary production. They provide not only a food source for animals, but also affect microbial ecosystems through symbioses with microorganisms or secretion of some metabolites. Derived from amino acids, polyamines are present in almost all types of organisms, where they play important roles in maintaining physiological functions or against stress. Microalgae can produce a variety of distinct polyamines, and the polyamine content is important to meet the physiological needs of microalgae and may also affect other species in the environment. In addition, some polyamines produced by microalgae have medical or nanotechnological applications. Previous studies on several types of microalgae have indicated that the putative polyamine metabolic pathways may be as complicated as the genomes of these organisms, which contain genes originating from plants, animals, and even bacteria. There are also several novel polyamine synthetic routes in microalgae. Understanding the nature of polyamines in microalgae will not only improve our knowledge of microalgal physiology and ecological function, but also provide valuable information for biotechnological applications.